Absorption, Mentalizing, and Mysticism: Sensing the Presence of the Divine. (29th May 2019) - Coleman III, Thomas; Bartlett, James; Holcombe, Jenny; Swanson, Sally; Atkinson, Andrew; Silver, Christopher; Hood, Ralph
Abstract : Research suggests trait absorption, individual differences in Theoryof Mind (ToM), and orthopraxical training are importantfor explaining a variety of extraordinary experiences typicallyassociated with religion. However, no studies exist quantifyingToM ability or testing its relationship with trait absorption inthe prediction of what is arguably the most ubiquitous type ofextraordinary experience-the mystical experience. To addressthis, two exploratory studies were conducted using a sample ofmeditators (N = 269) and undergraduate students (N = 123). Instudy one, regression analyses revealed weekly religious/spiritualpractice, absorption, and mentalizing predict increased mysticalexperiences. Moreover, moderation analysis indicated theabsorption-mysticism relationship is stronger among individualswith lower mentalizing ability. Study two only replicated therelationship of absorption and weekly practice with mysticism.These studies highlight the robust contribution of absorption inmystical experiences and suggest a more dynamic role for mentalizingthan is accounted for in the current literature.